Toward a Microeconomics of Growth. - Burgess, R; Venables, A (World Bank, 2004)
What drives growth at the microeconomic level? Burgess and Venables divide the factors that determine a location's growth performance into two groups, '1st advantage' and '2nd advantage.' The term 1st advantage refers to the conditions that provide the environment in which new activities can be profitably developed, including most of the factors on which traditional theory has focused, such as access to inputs (labor and capital), access to markets, provision of basic infrastructure, and the institutional environment. The term 2nd advantage refers to factors that increase returns to scale and can lead to cumulative causation processes. They may be acquired by learning, through technological spillovers, or by the development of thick markets of suppliers and local skills. The authors' analysis suggests that empirical investigation of the drivers of growth must shift down to a more microeconomic level. Such an analysis has become more feasible as data at the subnational level have become more available. By viewing recent empirical evidence on drivers of growth through their analytical framework, the authors are able to begin to sketch out a microeconomic agenda for growth. They emphasize that it is the manner in which 1st and 2nd advantages interact that shapes the pattern of development. The authors then turn to the example of how policy has affected manufacturing growth performance in India. They analyze links between the direction of state-level labor regulation and growth in the organized manufacturing sector, how state-led expansion of bank branches into rural areas has affected unregistered or informal manufacturing, and how the pre-reform technological capability of industries affected their response to liberalization in 1991. The analysis suggests that policy choices at the local level affect growth. Both theory and empirics need to downshift to the microeconomic level if we are to make advances in identifying specific means of encouraging innovation and growth. This paper is a product of Partnerships, Capacity Building, Development Economics Senior Vice Presidency.